Boran steer growth rates on medium quality ranch pasture (Laikipia) and feedlot (Lanet) - Hall, John; Mukhebi M.W. (1971)
237 Boran steers aged between 2¼-3 years with an average body weight of 209.5kg were bought and kept in Laikipia and Lanet stations for fattening purpose. The steers were kept in Laikipia weigh 274.7kg after 111 days and 290.6 kg after 159 days. And those steers in Lanet weigh 312kg after 35 days and 323.5kg after 56 days.